The role of nurses in dealing with hypertensive patients in primary health care - Santos, Rafael de Carvalho dos; Espinoza, Isabela Marins; Gomes, Julia de Oliveira (Seven Editora, 2024)
Arterial hypertension (AH) is a multifactorial chronic pathology and, therefore, can affect individuals of different age groups and different groups in society. In Brazil, AH has been growing significantly and has become one of the protagonists in mortality rates in the country. Due to this, a question was raised to better understand what the role of nurses would be in relation to hypertensive patients in basic health, therefore the objective of this study is to describe the role of nurses in a qualified and effective way in caring for patients with arterial hypertension, with the aim of promoting comprehensive health care for these individuals,  and also contributing scientifically to the journey and knowledge of professionals and future nursing professionals so that, through this, assistance to these clients occurs in a more assertive and effective way. To carry out this study we used the literature review methodology. During the research we came across a total of 40 articles on this topic, it was necessary to discard 16 because they were out of date and we used 24 to write and compose this study. We have seen that through prevention it is possible to avoid or delay the development of the pathology, and with adequate treatment the patient's life expectancy and quality of life increases considerably, improving their prognosis. We conclude that for this, the nurse has great importance in the health and disease process, paying attention to the signs and symptoms, family history, patient's lifestyle and socioeconomic condition to be able to carry out the screening, maintenance and prevention of arterial hypertension, thus avoiding, possible complications and damage to the individual’s health. DOI:https://doi.org/10.56238/sevened2024.001-006